2016
DOI: 10.3329/baj.v19i1.29863
|View full text |Cite
|
Sign up to set email alerts
|

Yield Response and Nitrogen use Efficiency of Boro Rice Varieties as Affected by Different Methods of USG and Prilled Urea Application

Abstract: An experiment was conducted at the Bangladesh Rice Research Institute (BRRI), Gazipur during Boro season of 2013-14 and 2014-15 to find out the nitrogen use efficiency and yield of boro rice var. BRRI dhan28 and BRRI dhan29 under four N management practices such as application of prilled urea using prilled urea applicator, application of USG (2.7gm) using USG applicator, broadcasting of prilled urea following three splits and a control (without urea). The experimental design was RCBD replicated thrice. BRRI dh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…LSD: Least significant difference at 5%, CV: Coefficient variation the absence of other macro and micro nutrients (S, Zn and B). a similar trend has been reported in another study 13 . Application of 200 kg NPSZnB+150.2 kg N haG 1 increased grain yield by 135.5 and 111.1% over control and 100% recommended NP, respectively.…”
Section: Resultssupporting
confidence: 92%
“…LSD: Least significant difference at 5%, CV: Coefficient variation the absence of other macro and micro nutrients (S, Zn and B). a similar trend has been reported in another study 13 . Application of 200 kg NPSZnB+150.2 kg N haG 1 increased grain yield by 135.5 and 111.1% over control and 100% recommended NP, respectively.…”
Section: Resultssupporting
confidence: 92%
“…The highest harvest index (49.43%) obtained in CF + T 6 (USG, 7 DAT) whereas the lowest value (45.74%) recorded in CF + T 1 (Control) (Table 5). When the application of USG was compared with PU, a non-significant interaction effect on the harvest index of BRRI dhan28 and BRRI dhan29 was found by Bhuiyan et al (2016) and the grain harvest index ranged from 0.40 to 0.52 in BRRI dhan28 and 0.42 to 0.54 in BRRI dhan29. Similarly, Mboyerwa et al (2021) revealed that the harvest index was significantly affected by N levels, which ranged from 0.45 to 0.53, but irrigation methods had little influence (p > 0.05).…”
Section: Harvest Index (%)mentioning
confidence: 96%